(untitled) (Nonconventional Technologies Review, 2020)
The field of nonconventional technologies, with the new challenges and the new solutions offered, have generated, at least in the last years, the market presentation of some inventions in different stages. Patent requests, patents, prototypes are launched but the lack of material support, lack of funding can determine the inventors to feel less motivated, and this aspect is more frequently taken into consideration by national and European bodies in the sense of trying to find solutions for financial or educational support, unitary solutions that could determine the safety of technological transfer.